Analisis Penerimaan Retribusi Pemakaman Pada Dinas Lingkungan Hidup Kota Makassar - Rahmat Hidayat; Djusdil Akrim; Veronika Sari Den Ka (PT Bone Jaya Kreatif, 2022)
Retribution is a regional levy as a payment for services or the granting of certain permits specifically provided and/or granted by the Regional Government for personal or corporate purposes. This study aims to determine the procedure for payment of funeral service fees and the realization of their acceptance at the Makassar City Environmental Service. The types of data used in this study are qualitative and quantitative data, with primary data sources or data originating from the original or first sources and secondary data, with data collection procedures through interviews and observations using qualitative descriptive data analysis techniques with three stages namely ( 1) Data reduction stage, (2) Data presentation stage. (3) draw conclusions. The results of this study indicate that in terms of payment of retribution for funeral services, the obligatory Retribution has been given an understanding of the procedure for payment through outreach so that the obligatory levy, knows more about the payment procedure. The increase in retribution receipts in the last 2 years was due to an increase in outreach by cemeteries conducting outreach to obligatory retribution through RT/RW